2015
DOI: 10.1364/oe.23.001081
|View full text |Cite
|
Sign up to set email alerts
|

An 116 W output, 6 kHz linewidth, single-polarization EDFA-MOPA system with a ^13C_2H_2 frequency stabilized fiber laser

Abstract: We demonstrate a record high CW output power of 11.6 W and an ultra-narrow linewidth of 6 kHz in an all-fiber master oscillator and power amplifier (MOPA) fiber laser system. The master oscillator is a (13)C(2)H(2) frequency-stabilized single-polarization fiber laser with a 100 mW output. The power amplifier section consists of a core-pumped polarization-maintained erbium-doped fiber pumped by a 1480 nm cascaded Raman fiber laser. A total electric-to-optical conversion efficiency with a record high value of 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In MOPA configuration, a low-power narrow linewidth seeder is amplified through several stages until the high output power is reached [11]. High-power narrow linewidth MOPA laser research near 1.5 µm, a 151 W output power with 1 MHz linewidth fiber MOPA laser [12], a 10.9 W kHz-linewidth one-stage all-fiber linearly-polarized MOPA laser at 1560 nm [13], an 11.6 W output power with 6 kHz linewidth single-polarization EDFA-MOPA system [14], a 56.4 W output power with 4.17 kHz linewidth MOPA laser [15], and a 23 W output power with 1.7 kHz linewidth MOPA laser [16] are reported.…”
Section: Introductionmentioning
confidence: 99%
“…In MOPA configuration, a low-power narrow linewidth seeder is amplified through several stages until the high output power is reached [11]. High-power narrow linewidth MOPA laser research near 1.5 µm, a 151 W output power with 1 MHz linewidth fiber MOPA laser [12], a 10.9 W kHz-linewidth one-stage all-fiber linearly-polarized MOPA laser at 1560 nm [13], an 11.6 W output power with 6 kHz linewidth single-polarization EDFA-MOPA system [14], a 56.4 W output power with 4.17 kHz linewidth MOPA laser [15], and a 23 W output power with 1.7 kHz linewidth MOPA laser [16] are reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, in these previous reports, the linewidth of the laser was not taken into consideration. As the important narrow linewidth regime wavelength neared 1550 nm, 11.6 W output power at 1538.8 nm with linewidth of 6 kHz pumped by a 1480 nm cascaded Raman fiber laser [12], 10.9 W output power at 1560 nm with linewidth of 3.5 kHz [13], 56.4 W with a linewidth of 83.5 kHz at 20 dB [14], and a 23 W single-frequency laser obtained with a laser linewidth of 1.7 kHz were reported [15]. It can be seen that the linewidth increased with the improvement of output power.…”
Section: Introductionmentioning
confidence: 99%
“…High power single frequency lasers/amplifiers with near diffraction limited beam quality have been found to be widely applicable in many applications, such as coherent beam combining, gravitational wave detection (GWD), Doppler-Lidar, nonlinear frequency conversion and so forth [1][2][3][4][5][6][7]. Nevertheless, previous publications showed that power scaling of this type of monolithic system is limited by the backward stimulated Brillouin scattering (SBS) effect [1,8].…”
Section: Introductionmentioning
confidence: 99%